P0095 Trends in cure proportion of major cancer sites in Japan between 1993 and 2006 (J-CANSIS study): An observational study. (July 2015) - Ito, Y.; Miyashiro, I.; Hattori, M.; Nishino, Y.; Ioka, A.; Nakayama, T.; Rachet, B.
Abstract : Background: Cure proportion is an important statistic for cancer patients and clinicians. However, these data were scarce in Japan and other Asian countries. We aimed to report trends in cure proportion and median survival time (MST) for patients who still have cancer after treatment (uncured patients) to evaluate the improvement in cancer treatment in Japan. Methods: The J-CANSIS study was a collaborative observational study of cancer survival in Japan, and used population-based cancer registry data. We used 791, 284 patients' data from six prefectural cancer registries (Yamagata, Miyagi, Fukui, Niigata, Osaka, and Nagasaki). We applied flexible parametric cure models to estimate cure proportion and MST for uncured patients with major cancer types (ie, stomach, colorectal, liver, lung, breast, cervix, and ovary) at diagnosis (during 1993–97, 1998–2001, and 2002–06), sex, and by age. We selected an adequate model based on its fitting and likelihood-ratio test for all six cancer sites. Findings: Cure parameters could not be estimated for uncured patients with breast cancer and the cure models fitted poorly to those with liver cancer (all age groups) or colorectal cancer (aged 75 years or older). The cure proportion of patients with stomach cancer was not substantially improved over the diagnosis periods; MST increased by a few months in the latest period (2002–06). From first to last period the cure proportion of those with ovarian cancer improved by 5.8–12.9%. Lung cancer showed different trends among sexes; the cure proportion improved more for women (9.5–14.7%) than for men (2.9–6.5%). Interpretation: Cure proportion for women with ovarian cancer or lung cancer improved considerably, which was probably due to the improvement in cancer treatment with time.